Comparison between Curcumin and Lycopene in Management of Oral Submucous Fibrosis in Terms of Burning Sensation and Mouth Opening - Noor, Javeria; Khalid, Muhammad Usman; Usama, Malik Muhammad (Indus Journal of Bioscience Research, 2025)
Background & Objective: Oral submucous fibrosis (OSMF) is a chronic, potentially malignant condition characterized by burning sensation and progressive limitation of mouth opening. Curcumin and lycopene are natural antioxidants explored for their therapeutic benefits in OSMF. The objective of our study was to compare curcumin and lycopene in treatment of oral submucus fibrosis in terms of mean mouth opening and mean burning sensation. Methodology: This comparative cross-sectional study was conducted at the Department of Oral and Maxillofacial Surgery, Allied Hospital, Faisalabad. Sixty patients diagnosed with OSMF were randomly assigned into two groups: Group A received lycopene (10 mg twice daily), while Group B received curcumin (500 mg thrice daily) for six weeks. Pre- and post-treatment assessments of burning sensation (using VAS score) and mouth opening (in centimeters) were performed. Results: Baseline characteristics were comparable except for gender (more males in Group B, p = 0.008) and Gutka use (higher in Group A, p = 0.028). Group A (Lycopene) showed significantly greater improvement in burning sensation (p = 0.027) and mouth opening (start: p = 0.022; end: p < 0.001). Conclusion: Both curcumin and lycopene are effective in the management of OSMF. Curcumin offers superior symptomatic relief, while lycopene shows greater improvement in mouth opening. Combination therapy may enhance therapeutic outcomes and warrants further investigation.